Society’s Denial on Jane Eyre’s Autonomy and Subjectivity: A Martha Nussbaum’s Critical Reading - R Hariyani Susanti (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
Martha Nussbaum's objectification theory provides a lens for analyzing the experiences of the main character, Jane, in Charlotte Bronte's "Jane Eyre." This literary study aims to analyze the type of objectification suffered by Eyre by applying Nussbaum’s theory. According to this theory, objectification occurs when a person is reduced to a mere object for someone else's use and is not recognized as an autonomous being with their own desires and interests. In the novel and TV adaptation, Jane is subjected to objectification by several characters, including Mr. Rochester, who tries to mold her into the perfect wife, and St. John Rivers, who views her as a tool for his missionary work. Through these experiences, Bronte highlights the damaging effects of objectification and the importance of valuing individual dignity and agency. By demonstrating the harm caused by treating people as objects, the novel serves as a critique of the societal norms that perpetuated such treatment and reinforces the importance of treating all individuals with respect and empathy